34‐2: Distinguished Paper: Development of 55inch 8K AMOLED TV by Inkjet Printing Process. Issue 1 (25th September 2020) - Wu, Zhongyuan; Yan, Liangchen; Li, Yongqian; Shih, Huaiting; Feng, Xuehuan; Kim, Taejin; Peng, Yuqing; Yu, Jianwei; Dong, Xue
Abstract : In this paper, we presented 55 inch 8K4K AMOLED TV employing coplanar Oxide TFT backplane, top emissive inkjet‐printing OLED device, Gate Driver on Array(GOA) and compensation technologies. It is so far the largest prototype AMOLED TV fabricated by using inkjet printing process with 8K resolution. It shows the stunning display quality thanks to the high resolution and fast refresh frequency. It proves that the inkjet printing process is not only cost competitive but also can deliver premium display.